Discovery of Orally Bioavailable Phthalazinone Analogues as an ENPP1 Inhibitor for STING-Mediated Cancer Immunotherapy - Cho, Yeonguk; KANG MISO; Ji suhyun; Jeong, Hee Jin; Cheong Jaeeun; Oh, Do Hee; Park, Sunyoung; Park, Yong-Yea; Choi, Junghwan; Kim, Sungjoon; Kim, Nam-Jung; Lee, Duck-Hyung; et al. (American Chemical Society, 2023)
A lack of the T cell-inflamed tumor microenvironment limits the efficacy of immune checkpoint inhibitors (ICIs). Activation of stimulator of interferon genes (STING)-mediated innate immunity has emerged as a novel therapeutic approach in cancer therapy. 2′,3′-Cyclic GMP？AMP (cGAMP) is a natural STING agonist; however, cGAMP is subjected to endogenous degradation by ecto-nucleotide pyrophosphatase phosphodiesterase 1 (ENPP1). To improve the ICI response rate, we developed 29f, a novel ENPP1 inhibitor with phthalazin-1(2H)-one as the core scaffold. 29f inhibited the cGAMP hydrolysis by ENPP1 in vitro (IC50 = 68 nM) and enhanced the STING-mediated type I interferon response in both immune and tumor cells. 29f demonstrated excellent metabolic stability and bioavailability (F = 65%). Orally administered 29f promoted tumor growth inhibition in a CT26 syngeneic model and increased the anti-PD-L1 response. Furthermore, 29f-induced immunological memory prevented the tumor relapse against tumor rechallenge, suggesting the promising therapeutic potential of 29f.